(untitled) (FUDMA JOURNAL OF SCIENCES, 2021)
The removal of (Cr) ions from industrial wastage by adsorption on rice husk was investigated based on activated pure rice husk dosage, stay time, metal concentration and solution temperature. The optimum values of activated pure rice husk dosage and stay time were determined to be 0.5gm/50ml solution and 60 mins, respectively, for the adsorption of (Cr) ions. The constant for the Freundlich, D-R and Langmuir isotherms were 50%, calculated at 50 . The adsorption of (Cr) from industrial wastage was found to be exothermic. Thermodynamic parameters such as free energy change ( G°), enthalpy change ( H°) and entropy change ( S°) of adsorption also calculated and interpreted from the slope and intercept of the plots of lnkD vs I/T. The G° value decreases with rise in temperature and the negative values of H° indicate that the adsorption of (Cr) from industrial wastage was an exothermic process while positive values of change in entropy ( S°) were also observed